Archaeological Landscape of the Nile Valley Civilization in Early Egypt - Dr Kundan Kumar (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
The presence of the NileRiver and the NileRiverValley in Ancient Egypt greatly influenced the culture of its people. The ancient Egyptians began with small settlements around the NileRiver and were able to make permanent settlements only because of the presence of the Nile. As the Egyptian civilization grew, it became even more dependent on the Nile and its role in their economy. Finally, because of the Ancient Egyptian dependence on the NileRiver, it became a centerpiece of their religious practices and their belief in the afterlife. These are a few of the major ways that the NileRiver played a significant role in Ancient Egyptian culture